Another survey on etched porcelain laminate veneers in aesthetic dentistry - F Farshchian (Tehran University of Medical Sciences, 1989)
In some clinical interventions, there have been some doubts on replacing resin veneers by etched porcelain veneers. Never the less, Public awareness and demand for more aesthetic treatments caused increased usage of laminate veneers in operative treatments as routine treatment method. Dental material companies have rapidly produced newer materials to replace the old ones and respond the needs. Thus, dental science has developed in aesthetic operative dental science. Each novel treatment modality requires modern material and methods that needs experience and knowledge in order to eliminate the complications. Many clinical researches on durability and guidelines of each method have been conducted.  Porcelain veneers require limited tooth preparation and brings high esthetic. In addition, their function and durability are acceptable and their favorable path of insertion is compatible to periodontal tissues.